Nursing student's perspectives and academic performance in anatomy and physiology before, during and after a stability period of COVID-19 - Narnaware, Yuwaraj; Cuschieri, Sarah (My University, 2023)
The Coronavirus disease 2019 (COVID-19) has dramatically disrupted medical, allied health, and nursing education worldwide. It has created challenges for students and educators by requiring a sudden shift to online teaching and learning activities from didactic, passive teaching and learning. The objective of the present study was to evaluate the impact of these modes of teaching and learning before, during, and after the transition through COVID-19 on the class average and Grade Point Average (GPA) of nursing students taking anatomy and physiology in the first year of nursing. Using the virtual teaching and learning modality, the present study demonstrated that the mean class average of anatomy and physiology midterms and final examinations during COVID-19 (synchronous online teaching) was significantly higher (P<0.001) compared with the pre-COVID-19 (face-to-face (F2F) teaching) class average. However, the class average and GPA were not different between pre-COVID-19 (F2F teaching) and post-COVID-19 (hybrid/flex teaching). Virtual teaching of these subjects also significantly (P<0.001) increased the students’ GPA in anatomy and physiology during COVID-19 compared to before and after the stability of COVID-19. Students’ perspectives on teaching and learning these courses using these teaching modalities indicated that nursing students prefer a synchronous, hybrid mode of learning in anatomy and physiology. The present study demonstrates nursing students’ preference for a synchronous, online and hybrid mode of teaching and learning anatomy and physiology in case of the re-emergence of a new strain of coronavirus after Omicron variant in future lockdown due to the COVID-19 pandemic.
Keywords: nursing; anatomy; physiology; COVID-19; Omicron; pandemics